2022
DOI: 10.3390/ijerph191912190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Balance Training on Muscle Tone and Balance Ability in Adult Men and Women

Abstract: (1) Background: The amount of physical activity most adults perform is less than the recommended amount, and the resulting decrease in physical strength makes them vulnerable to various diseases. A decrease in muscle size and strength due to damage caused by disease or aging negatively affects functional strength. Muscle evaluation in adults can yield results that are predictive indicators of aging and unexpected disability. In addition, balance ability is essential to prevent falls and injuries in daily life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An analysis of the correlation between the core muscle endurance and static balance in adults with FHP revealed strong positive correlations in trunk flexion, extension, right flexion, left flexion endurance, and static balance [64]. Female and male university students performed core balance exercises for 10 weeks [65]. They reported that static and dynamic balance were significantly improved [65].…”
Section: ⅳ Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An analysis of the correlation between the core muscle endurance and static balance in adults with FHP revealed strong positive correlations in trunk flexion, extension, right flexion, left flexion endurance, and static balance [64]. Female and male university students performed core balance exercises for 10 weeks [65]. They reported that static and dynamic balance were significantly improved [65].…”
Section: ⅳ Discussionmentioning
confidence: 97%
“…Female and male university students performed core balance exercises for 10 weeks [65]. They reported that static and dynamic balance were significantly improved [65]. An exercise program, including bridge exercise and quadruped with arm and leg extension using foam roller exercise, was performed for elderly people over 60 years for five weeks [66].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In the future, we aim to include in the analysis a larger group of patients for a longer period, as well as the assessment of postural stability in relation to myotonometric parameters. As the postural stability and physical activity was already studied in healthy subjects [34,35], it can be extended to patients suffering from Parkinson's disease. The correlations among dynamic balance, physical activity and quality of life have been investigated [36], as well as the efficacy of particular trunk exercises in the balance training in patients with Parkinson's disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle stiffness of an appropriate level is necessary to maintain dynamic stability, and it has been shown that active muscle stiffness is vital in ensuring greater joint stability and preventing unfavorable factors that can lead to traumatic joint displacement [ 13 ]. If the stiffness is too high, there is an increased risk of injury due to reduced flexibility, and the risk of muscle weakness increases if the stiffness is too low [ 14 ]. Increased muscle tension leads to an increase in intramuscular pressure, impairing cardiovascular function and restricting blood flow to the muscles, which causes hypoxia and results in the process of muscle fatigue and slower recovery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%